1968, 1989, 2011: reconsidering social movements, 'moments of change' and theoretical framing over time - Kornetis, Kostis (Historein, 2013)
This article focuses on three separate "moments of change" - 1968, 1989 and 2011 – in order to trace the changes in the way in which social movements were theoretically framed on a research level ever since the 1960s. Rather than focusing on the real or imaginary connections that activists often create with the contestatory past – or the rejection thereof – it demonstrates the ways in which those moments were theorised and the genealogies that were forged by specialists, who more often than not were implicated in the events themselves. In this respect, it argues that 1968 was the starting date that defined to a greater or lesser extent how we still view and experience collective mobilisations.